Characterization of aroma compounds of Pu-erh ripen tea using solvent assisted flavor evaporation coupled with gas chromatography-mass spectrometry and gas chromatography-olfactometry - Bei Wang; Qing Meng; Lin Xiao; Ruili Li; Chunhai Peng; Xueli Liao; Jingna Yan; Honglin Liu; Guanhua Xie; Chi-Tang Ho; Huarong Tong (Food Science and Human Wellness)
Pu-erh ripen tea becomes popular worldwide owing to its unique taste and aroma. In the present study, volatile compounds from Pu-erh ripen tea were extracted using a solvent assisted flavor evaporation (SAFE) and analyzed with a gas chromatography-mass spectrometry (GC-MS) and a gas chromatography olfactometry (GC-O). Results demonstrated that 58 major volatile compounds and 24 aroma active substances of Pu-erh ripen tea were identified by GC-MS and GC-O analysis. Among volatile compounds identified, methoxyphenyl compounds were considered as the dominate compounds in the aroma of Pu-erh ripen tea. Further investigation showed that 6 methoxybenzenes were responsible for the aging aroma in Pu-erh ripen tea; α-ionone, 3,4-dimethoxytoluene, 1,3-dimethoxybenzene, etc. were responsible for the wood-like aroma. Linalool, α-terpineol, α-ionone, β-ionone, and benzeneacetaldehyde were responsible for the ﬂoral odor. Compared the odor detection threshold (ODT) among the 8 methoxyphenyl compounds in water, 1,2,3-trimethoxybenzene showed the highest ODT, followed by 3,4-dimethoxyphenol. 1,3-Dimethoxybenzene (105 μg/L) and 1,2,3-trimethoxy-5-methylbenzene (100 μg/L) were present at relatively low odor threshold values. The result indicated that methoxyphenyl compounds play a vital role in the unique flavor of Pu-erh ripen tea.